1999
DOI: 10.1038/46580
|View full text |Cite
|
Sign up to set email alerts
|

Conserved regulation of proximodistal limb axis development by Meis1/Hth

Abstract: Vertebrate limbs grow out from the flanks of embryos, with their main axis extending proximodistally from the trunk. Distinct limb domains, each with specific traits, are generated in a proximal-to-distal sequence during development. Diffusible factors expressed from signalling centres promote the outgrowth of limbs and specify their dorsoventral and anteroposterior axes. However, the molecular mechanism by which limb cells acquire their proximodistal (P-D) identity is unknown. Here we describe the role of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
255
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(275 citation statements)
references
References 28 publications
19
255
0
1
Order By: Relevance
“…Meis2 encodes a homeobox transcription factor expressed in the lateral plate mesoderm and subsequently in the proximal limb mesoderm that is required as a determinant of proximal limb identity (31). In E9.0 Raldh2 Ϫ/Ϫ embryos we found that Meis2 expression was not detected in the lateral plate mesoderm and somites as normal but was still present in the hindbrain ( Fig.…”
Section: Ra Is Required For Initiation Of Forelimb Bud Developmentmentioning
confidence: 71%
“…Meis2 encodes a homeobox transcription factor expressed in the lateral plate mesoderm and subsequently in the proximal limb mesoderm that is required as a determinant of proximal limb identity (31). In E9.0 Raldh2 Ϫ/Ϫ embryos we found that Meis2 expression was not detected in the lateral plate mesoderm and somites as normal but was still present in the hindbrain ( Fig.…”
Section: Ra Is Required For Initiation Of Forelimb Bud Developmentmentioning
confidence: 71%
“…RA has also been proposed to control proximal to distal patterning of the limb via direct regulation of the proximally expressed Meis homeodomain proteins, Meis1 and Meis2 (Mercader et al, 2000(Mercader et al, , 2005. Overexpression of these genes leads to truncation of the distal limb (Capdevila et al, 1999;Mercader et al, 1999). Targeted disruption of Meis1 results in death at around embryonic day 14.5 in mice (Hisa et al, 2004;Azcoitia et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Key roles of this transcription factor are now documented both in normal development and disease formation (1)(2)(3)(4). Decreased MEIS1 levels are associated with Restless leg syndrome (RLS) (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased MEIS1 levels are associated with Restless leg syndrome (RLS) (5,6). Overexpression of MEIS1, on the other hand, has been linked to leukemia (3,4).…”
Section: Introductionmentioning
confidence: 99%